Merleau-Ponty: a experiência do corpo como ser sexuado - Schneider, Patrícia (2010)
The objective of this study is to analyze the conception of body and sexuality in a phenomenological-psychoanalytical perspective, and, from this reconstruction, to understand the notion of carnal unconscious in Merleau-Ponty, a notion that is being established from an articulation with the psychoanalytical theory. For this, the work has as an investigative base the first part of Phenomenology of Perception of Maurice Merleau-Ponty, capital text where it is explored the theme of the experience of the own body and its critical counterpoint to the traditional theories current in modern science and metaphysics. The Cartesian doctrine of the body is founded on the premise that the thought is prior to the perception, that is, the spirit has metaphysical and cognitive primacy over the body. The body is characterized for exercising a purely instrumental function in relation to the soul. Empiricism, however, bases the knowledge on sensory experience at which the body is defined as a piece of matter, an object of study of anatomy. However, Merleau-Ponty identifies, on these two canonical positions (intellectualism and empiricism), a convergence of base: a dualistic principle of conception, which camouflages the most characteristic experience of perceived phenomena, among them, the experience of the own body - dualism that splits our internal and external experience, spiritual and corporal. Thus, the tradition ends up masking the true experience of the body in such a way that the sexuality is only an instinct, an isolated physiological process, a predetermined mechanism. For the philosophical or even scientific tradition, the affection becomes an irrelevant issue, without receiving any ontological status more prominent. Differently, shows Merleau-Ponty, Freud has been the one that will launch new theoretical foundations in sense of rethinking more radically the experience of sexuality, considering the fact that everything that humans do has one or more sense or meaning. Thus, sexuality is not just an isolated physiological process, since the own man is understood as a cultural and historical being, a sense producer being, because the body reveals itself, in its latest radicalism, as a "sexual being". Without ever reducing itself to the object condition, the body becomes a source of meaning. It is a living experience. Sexuality becomes, therefore, the most genuine deflagration of this dialectical and paradoxical movement. So, this is a fundamental characteristic of embodiment that Freud already presumes in his clinical experience. Despite Freud's ambivalent relationship with philosophy, this study makes a laconic incursion in his theory, focusing on the notions of desire and unconscious, in order to reconstruct the problematic of the unconscious in Merleau-Ponty. This one, while recognizing the Freudian merit, criticizes and challenges some points, in order to propose his own notion of carnal unconscious. This proposal has as central axis the notion of carnality, which culminates in an ontological rehabilitation of the sensible and announces a challenge to the conception of unconscious structured as a language, typically Lacanian.